PROTOTYPE SOLAR TRACKER BERBASIS ARDUINO - Yanel, Karnova; Rozi Saferi (Lembaga Pengembangan Kinerja Dosen, 2023)
Solar radiation is the light – also known as electromagnetic radiation – that is emitted by the sun. The enormous amount of energy generated from sunlight makes solar cells a very promising alternative energy source for the future. Solar cells also have the advantage of being a practical energy source considering they do not require transmission because they can be installed in a modular manner at any location where they are needed. Various technologies have been developed in the process of making solar cells to reduce production costs to make them more economical. The aim of this research has been achieved, namely to design an Arduino-based solar tracking system, so that by using a solar tracker solar energy can be absorbed and produced more optimally than without using a solar tracker. This is proven based on the results of the Black box test. As for the results of testing the system in a black box, the result is that solar panels can move to follow the sunlight and produce maximum energy. So that this tool can be applied to all regions and can assist the government in efforts to overcome energy problems, especially optimizing alternative energy.